1999
DOI: 10.1002/(sici)1521-2254(199903/04)1:2<93::aid-jgm19>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus vector requires electrostatic interactions including heparan sulfate for efficient gene transfer in mammalian cells

Abstract: Electrostatic charges play a critical role during the first step in mammalian cell transduction mediated by a recombinant baculovirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
50
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 27 publications
5
50
1
2
Order By: Relevance
“…Continued analysis has shown that baculovirus can infect and mediate gene transfer to cell types other than hepatic cells (14,36,42,45). However, this system has not proven applicable to all cell types.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Continued analysis has shown that baculovirus can infect and mediate gene transfer to cell types other than hepatic cells (14,36,42,45). However, this system has not proven applicable to all cell types.…”
Section: Discussionmentioning
confidence: 95%
“…Although the binding motif responsible for baculovirus endocytosis in mammalian cells is currently unknown, heparan sulfate is required for efficient gene transfer (14). The data presented in this study demonstrate that at least in some cell types, such as hepatocytes, entry of the baculovirus may require contact with the basolateral surface.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Different studies have demonstrated that GP64 is essential for baculovirus transduction of mammalian cells (11). In mammalian cells, it has been shown that electrostatic interactions, heparan sulfate, and phospholipids are necessary for baculovirus binding to the mammalian cell surface (12).…”
mentioning
confidence: 99%
“…Although the specific interactions between baculovirus surface proteins and target cellular receptors are not exactly known, there is a hypothesis of virus binding via heparate sulphate residues 18 and phospholipids 19 supported by a large number of baculovirus-susceptible cell lines in vitro. 13 When considering the possible clinical use of baculoviruses, the transductional kinetics and suitable administration methods of baculoviruses in vivo have to be evaluated.…”
Section: Discussionmentioning
confidence: 99%